(untitled) (Applied Biological Research, 2014)
The present study was conducted to assess the effects of ginger, cinnamon, chicory and stevia extract-supplemented feeds on lipid profile in serum and egg yolk of Jabalpur colour birds. Fifty four Jabalpur colour birds of 32 weeks age were randomly divided into 9 groups of 6 birds each. One group (control) was fed normal basal feed whereas rest groups were fed on feeds supplemented with alcoholic extracts of various herbs, separately, at two levels each [ginger, cinnamon and stevia extract mixed with feed @ 2.5 and 5.0 g kg-1feed and chicory extract @ 1.25 and 2.5 g kg-1feed]. Blood samples were collected on 0, 14th, 28th, 42nd and 56th day and serum profile showed a decreasing trend on herbal supplementation as compared to control. The total lipid was low in birds fed chicory (2.5 g kg-1feed) and cinnamon (5 g kg-1feed) followed by ginger (5 g kg-1feed) and cinnamon (2.5 g kg-1feed). The serum cholesterol and triglycerides showed more decrease in cinnamon (5 g kg-1feed) and chicory (2.5 g kg-1feed) fed birds than other groups. The increase in mean HDL concentration was significant in birds fed cinnamon (2.5 g kg-1feed), and stevia (5 g kg-1feed) on 56th day. Low LDL and VLDL were observed in birds fed cinnamon (5 g kg-1feed). The lowest concentration of egg yolk lipid and egg yolk cholesterol was noticed on 56th day in birds fed cinnamon (5 g kg-1feed), however least egg yolk triglyceride was low in chicory (2.5 g kg-1feed) and cinnamon (5 g kg-1feed) fed birds.